Perinatal factors associated with neonatal thyroid-stimulating hormone in normal newborns - Seong Yong Lee (Korean Society of Pediatric Endocrinology, 2016)
PurposeThis study was to evaluate the effect of neonatal, maternal, and delivery factors on neonatal thyroid-stimulating hormone (TSH) of healthy newborns.MethodsMedical records of 705 healthy infants born through normal vaginal delivery were reviewed. Neonatal TSH levels obtained by neonatal screening tests were analyzed in relation to perinatal factors and any associations with free thyroxine (FT4) and 17-α hydroxyprogesterone (17OHP) levels.ResultsAn inverse relationship was found between TSH and sampling time after birth. Twin babies and neonates born by vacuum-assisted delivery had higher TSH levels than controls. First babies had higher TSH levels than subsequent babies. Birth weight, gestational age, maternal age and duration from the rupture of the membrane to birth were not related to neonatal TSH. There were no significant differences in TSH level according to sex, Apgar scores, labor induction, the presence of maternal disease and maternal medications. There was a positive association between TSH and 17OHP level but not between TSH and FT4 level. Multiple linear regression analyses showed that sampling time, mode of delivery, birth order, and 17OHP level were significant factors affecting neonatal TSH level.ConclusionNeonatal TSH levels of healthy normal newborns are related with multiple factors. Acute stress during delivery may influence the neonatal TSH level in early neonatal period.